Social Media Marketing Maintains Business Existence - Wiwik Handayani; Andreas Nugroho Sihananto (Nusantara Science and Technology Proceedings, 2022)
The purpose of a business is to show and maintain the company's existence in the long term. Efforts to maintain business continuity and existence in the competition are by adopting the latest technological developments. The development of the online business world, of course, impacts new differentiation to create and market a product of goods and services. The use of social media as a digital communication channel is every day among Indonesians. Social media is developing into the most popular communication media for now. Besides being used as a communication medium, social media is also used by business people to promote a product/service that is produced. In the current era, the use of social media has transformed into digital marketing tools and digital selling. This article aims to understand the relationship between social media marketing and maintaining a business's existence. The method used in this study is a literature review or literature review. Social media marketing is essential in overhauling business and communication through social media and networking, which is the fastest way to grow a business entity. In addition, social media marketing aims to increase product, brand, and even business awareness by using social websites, such as social networking, microblogging, and content sharing. The advantage of the development of social media-based information technology is that it helps business people achieve goals and maintain business existence in the era of industry 4.0. Social media can also grow the company's reputation in the long term and increase customer loyalty to the company. The study of social media marketing is significant because it maintains the company's sustainable growth.